PROTECTIVE ROLE OF AQUEOUS EXTRACT OF ATRIPLEX HALIMUS L. AGAINST BENZENE-INDUCED DAMAGE ON RENAL FUNCTION AND GLOMERULAR CELLS IN RATS - ZEGHIB, KHAOULA; BOUTLELIS, DJAHRA ALI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Benzene (BZ) is an important pollutant compound, present in both occupational and general environment that has been linked to adverse health effect. The aim of the current study was to investigate the curative and preventive effect of Atriplex halimus L. (Ah) extract against BZ-induced nephrotoxicity in rats. Methods: A total of 30 male albino Wistar rats were divided into five groups (n=6): Control, Ah, BZ, AhP+BZ, and BZ+AhC. BZ (100 mg/kg b.w) was added in their drinking water for 15 weeks. Ah (Aqueous Extract of aerial parts) was given by gavage during the past 30 days of BZ-exposed for curative treatment (AhC) and all the duration of BZ exposure in the animals for preventive treatment (AhP). Some biochemical, oxidative stress parameters, and histopathology of kidney tissue were studied. Results: Obtained results revealed that BZ exposure to rats caused a significant elevation in urea, creatinine, and malondialdehyde levels. Then, it led to reducing the glutathione level, catalase, and glutathione-S-transferase activities when compared to the control animals. Histopathological studies showed a massive damage in kidneys of the BZ-exposed rat. Our results showed that curative treatment of aqueous extract of Ah has a partial correction of the biochemical, oxidative stress parameters, and kidney morphology, but preventive treatment has a dramatic effect on the previous parameters. Conclusion: Results demonstrated the beneficial effects of Ah preventive treatment against stress oxidative and kidney damage induced by BZ.